Social ties and sustainability in neighborhood canteens: A care-based approach - Dyen, Margot; Michaud, Maxime (Frontiers in Sustainability, 2023)
This article proposes to study the mechanisms by which food, and particularly commensality, 12 generate social ties. It mobilizes the conceptual framework of care, and is based on a qualitative 13 methodology inspired by ethnography, to study neighborhood canteens. Two nonprofit 14 organizations were investigated, both having in common the willing to generate social ties 15 between people living or working in the same neighborhood through the sharing of meals. We 16 conducted participant observations and two sets of semi-structured interviews with stakeholders 17 of the structure, either managers, employees or members. The first series aimed at describing 18 the experiences of the participants and their sociocultural background. The second series used 19 the projective method of collages, in order to go deeper in the understanding of the relationships 20 between the members and with the structures. The results show that there are different postures 21 towards neighborhood canteens, between a desire to receive care and a desire to give care. We 22 thus identify that the search for care is based on the need for recognition, valorization and 23 reassurance ; and that the kind of social ties created and experienced by the stakeholders is 24 highly dependent on the compatibility of their expectations regarding care.